Abundance and Characterization of Microplastics in Main Urban Ditches Across the Bahir Dar City, Ethiopia - Mhiret Gela, Sahlu; Aragaw, Tadele Assefa (Frontiers in Environmental Science, 2022)
Microplastics (MPs) pollution in water bodies, wastewater, and sewage is of concern due to their probable effects on the environment and human health. This study is a first-time attempt to evaluate the MPs occurrence, abundance, characteristics, and polymeric types in sediment and agglomerated sewage water from several urban ditches of Bahir Dar, Ethiopia in two-class sizes (i.e. >0.5 mm and <0.5 mm). Out of the total of 239 MPs particles, 61.09 % were of < 0.5 mm and this dominant fraction was of fragment shapes and transparent. The mean abundances of < 0.5 mm particles were 5 ± 1.00 items/50g in sediment and 3.00 ± 1.00 items/ml in Agglomerated sewage water. Similarly, the abundances of >0.5 mm fractions were 2 .33 ± 0.58 items/50g in sediment and 1.33 ± 0.58 items/ml in Agglomerated sewage water. Polyethylene (PE), Polypropylene (PP), polyethylene terephthalate (PET), Polystyrene (PS), polyamide (PA), and polyvinylchloride (PVC), were the most detected ones. However, PET and PVC were not detected in agglomerated sewage water samples.